Virulence regulation of Zn2+ uptake system znuABC on mesophilic Aeromonas salmonicida SRW-OG1 - Wang, Jiajia; Xiu, Lijun; Qiao, Ying; Zhang, Youyu (Frontiers in Veterinary Science, 2023)
Psychrophilic Aeromonas salmonicida could not grow above 25 ℃ and therefore thought unable to infect mammals and humans. In our previous study, a mesophilic A. salmonicida SRW-OG1 was isolated from Epinephelus coioides with furunculosis. Through the analysis of preliminary RNA-seq, it was found that the Zn2+ uptake related genes znuA, znuB and znuC might be involved in the virulence regulation of A. salmonicida. Therefore, the purpose of this study was to explore the effect of znuABC silencing on the virulence regulation of A. salmonicida SRW-OG1. The results showed that the growth of the znuA-RNAi, znuB-RNAi, and znuC-RNAi strains was severely restricted under the Fe2+ starvation, but surprisingly there was no significant difference under the Zn2+ restriction. In the absence of Zn2+ and Fe2+, the expression level of znuABC was significantly increased. The motility, biofilm formation, adhesion and hemolysis of the znuA-RNAi, znuB-RNAi, and znuC-RNAi strains were significantly reduced. We also detected the expression of znuABC under different growth periods, temperatures, pH, as well as Cu2+ and Pb2+ stresses. The results showed that znuABC was significantly up-regulated in the logarithmic phase and the decline phase of A. salmonicida. Interestingly, the trend of expression levels of the znuABC at 18 ℃, 28 ℃ and 37 ℃ was reversed to another Zn2+ uptake related gene zupT. Taken together, these indicated that the znuABC was necessary for A. salmonicida SRW-OG1 pathogenicity and environmental adaptability, and was cross regulated by iron starvation, but it was not irreplaceable for A. salmonicida SRW-OG1 Zn2+ uptake in the host.